Design, validity and reliability of an Environmental Awareness Scale. - Aliaga-Herrera, Cecilia (2022)
As part of a study of "environmental awareness and artistic expression in students of a public university in Metropolitan Lima", the objective was to design and determine the validity of the items and the reliability of a scale to assess environmental awareness. The sample consisted of 216 volunteer students, 63 men and 153 women, aged between 17 and 30 years, selected by non-probabilistic purposive sampling. In this section, the design corresponds to an instrumental study. The respondents answered the Environmental Awareness Scale virtually: the Exploratory Factor Analysis was used, by means of the Principal Axes Factorization method, with Varimax rotation, allowing the estimation of certainty of validity of the items based on the internal structure. On the other hand, the Confirmatory Factor Analysis led to identify that the CFI and TLI (0.923 and 0.910, respectively) exceeded the value of 0.90 and are therefore considered acceptable. The SRMR (0.057) and RMSEA (0.052), reached mean values close to adequate. Finally, the Chi-square was 1.589, representing an acceptable value. Regarding the reliability of the inventory, the Alpha (.85) and Omega (.90) coefficients are above the acceptable range.